2021
DOI: 10.1007/s11356-021-13411-w
|View full text |Cite
|
Sign up to set email alerts
|

Chlorella vulgaris or Spirulina platensis mitigate lead acetate-induced testicular oxidative stress and apoptosis with regard to androgen receptor expression in rats

Abstract: The current research was constructed to throw the light on the protective possibility of Chlorella vulgaris (C. vulgaris) and Spirulina platensis (S. platensis) versus lead acetate-prompted testicular dysfunction in male rats. Forty rats were classi ed into four groups; i) control, ii) rats received Lead acetate (30 mg/kg bw), iii) rats were concomitantly received Lead acetate and C. vulgaris (300 mg/Kg bw), vi) rats were simultaneously treated with Lead acetate and S. platensis (300 mg/Kg bw) via oral gavage … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 97 publications
0
11
1
Order By: Relevance
“…Furthermore, Huang et al [ 149 ] demonstrated that PbAc induced a dose-dependent reduction in AR expression in the spermatogenic cells, Sertoli cells, and Leydig cells. Given this, Pb is a known endocrine disruptor with estrogenic properties, and it may be responsible for antagonizing AR expression in male Wistar rats [ 42 , 150 , 151 ]. The decrease in testicular AR expression observed in PbAc-exposed rats may also be explained by a reduction in serum testosterone levels [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Huang et al [ 149 ] demonstrated that PbAc induced a dose-dependent reduction in AR expression in the spermatogenic cells, Sertoli cells, and Leydig cells. Given this, Pb is a known endocrine disruptor with estrogenic properties, and it may be responsible for antagonizing AR expression in male Wistar rats [ 42 , 150 , 151 ]. The decrease in testicular AR expression observed in PbAc-exposed rats may also be explained by a reduction in serum testosterone levels [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phycocyanin can scavenge loose radicals along with alkoxyl, hydroxyl, and peroxyl radicals. It additionally reduces nitrite manufacturing and inhibits the expression of inducible nitric oxide synthase (iNOS), as severa research have shown (Ibrahim et al,2021, Roy and Pabbi,2022,Li et al,2022.…”
Section: 85±015bmentioning
confidence: 99%
“…Recently, it was highlighted that C. vulgaris or S. platensis can have positive effects on testicular dysfunction provoked by lead acetate due to their antioxidant activity, immunomodulatory ability, and anti-apoptotic activity [182].…”
Section: Microalgae and Algaementioning
confidence: 99%